Modification and characterization of phytase for animal feed production - Noorbatcha, Ibrahim Ali; Samsudin, Nurhusna; Mohd. Salleh, Hamzah (Asian Network for Scientific Information, 2009)
Phytases catalyze the hydrolysis of inorganic phosphate from phytic acid and are able to improve the nutritional quality of phytate rich diet. Monogastric animal such as poultry and fish have lack of significant activity to hydrolyze phytate that contribute to elimination of beneficial nutrient for growth therefore contribute to land pollution, eutrophication of ground water and aquatic environment. Besides, it leads to the negative effect on vitamin utilization that lead to the emaciation, retarded growth and reproductive failure to animal. Due to the importance of, microbial sources for the commercial production of phytases, we have selected waste water bacterium phytase as the subject of interest in this study. In silico experiment is used to identify and examine the active site of waste water bacterium phytase. The factors influencing the ligand binding strength in the active site is analyzed and computational site directed mutagenesis experiments were carried out to evaluate the effects of mutations on the binding strength. Multiple mutations of M216R/E219R/H17A, M216R/E219R/F254E and some other multiple mutations showed improvement in the binding strength, primarily due to the addition of hydrogen bond with the adjacent residues. Automated docking based on genetic algorithm is used to dock the phytate in the active site and Partial Mean Force (PMF) scoring is used to calculate the strength of the binding before and after mutation.